A Rare Case of Primary Bilateral Adrenal Lymphoma - Veeraraghavan Meyyur Aravamudan; Phang Kee Fong; Yang Shiyao Sam; Pavel Singh; Siok-Bian Ng; Gollamudi Satya Pavan Kumar (Case Reports in Medicine)
Lymphoma may involve the adrenal glands, but primary lymphoma is rare. Only a few cases have been reported in medical literature. Primary adrenal lymphoma is extremely rare, accounting for <1% of non-Hodgkin lymphomas. We here present a case of a middle-aged female who presented with persistent fever for three weeks. She also reported significant weight loss of more than 10 kgs over the duration of three months. Computed tomography of the thorax and abdomen and pelvis demonstrated bilateral adrenal masses. She underwent short Synacthen test which showed evidence of adrenal insufficiency. She underwent CT-guided adrenal gland biopsy. Histology of adrenal gland biopsy showed features consistent with diffuse large B-cell lymphoma. She was started on R-CHOP chemotherapy and had a good clinical response and remained in complete remission for five months after chemotherapy.